Environmental assessment in the current scenario and with carbon credits: La Cortadera moor, department of Boyacá, Colombia - Vargas Terranova, Camilo Andrés; González Diaz, Javier Mauricio; Rueda Ramírez, Mónica Alexandra (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This study assessed the environmental and socioeconomic conditions of the La Cortadera moor in order to identify the environmental impacts to be considered in the provision of the carbon capture service. Using the methodology of the Secretaría Distrital de Medio Ambiente (2013) for environmental assessment and evaluation, two scenarios were proposed, the current and one with carbon credits, in order to compare how the provision of the capture service contributes to the recovery and conservation of the environment. Among the results, 82 impacts were identified in the current scenario, where significant, temporary and mitigable adverse impacts related to the anthropic activities carried out in the moor predominate; while in the scenario with carbon credits, 30 environmental impacts associated with the biotic, abiotic and socioeconomic environments were identified, of which 25 are positive and are classified mostly as significant and of high importance, linked to activities of administration of the protected area, institutionalism, research, generation of knowledge and strengthening of the socioeconomic and cultural component. According to the negative impacts of the current scenario (90%), the moor has been affected and fragmented to a considerable degree, mainly due to the expansion of the agricultural frontier. For this reason, as shown by the results in the scenario with carbon credits (83% positive impacts), the structuring of a protocol for the provision of the capture service in the ecosystem and the environmental management plan to mitigate the identified impacts would contribute to its recovery, conservation and sustainable development.